(untitled) (KULT_online, 2009)
In her postdoctoral lecture qualification, Silke Horstkotte explores the importance of photography for the representation and problematisation of memory in literature, particularly memories of the Second World War and the Holocaust. Horstkotte systematically analyses individual photographs in conjunction with literary excerpts which reproduce or refer back to them, thereby revealing levels of intermediality. By this means, Horstkotte exceeds her original research goal and contributes to a deeper understanding of the works of W.G. Sebald, Ulla Hahn, Monika Maron and other writers.